Pengaruh Ukuran Perusahaan, Profitabilitas, Solvabilitas, dan Ukuran Kantor Akuntan Publik terhadap Audit Delay - Karina Harjanto (Ultima Accounting : Jurnal Ilmu Akuntansi, 2017)
The purpose of this research is to examine the effect of company’s size, profitability, solvability, and the size of the accounting firm towards audit delay. The object in this research are property and real estate companies listed in Bursa Efek Indonesia (BEI) for the period 2013-2015. The sample is selected by purposive sampling method. There are 42 companies selected as sample. Data used in this research is a secondary data such as audited financial reports. Data analysis uses multiple linear regression. The result of this research shows that company’s size, profitability, and solvability have no influence on audit delay, while the size of accounting firm has significant positive influences on audit delay. The result also shows that company’s size, profitability, solvability, and the size of of the accounting firm simultaneously influence audit delay. Keywords: audit delay, company’s size, profitability, solvability, size the accounting firm